Political dynamics of Indonesia-Australia defence cooperation: Navigating geopolitical challenges in the Indo-Pacific - Wawan Darmawan; Sumadinata, R. Widya Setiabudi; Akim; Wawan Budi Darmawan (Research Journal in Advanced Humanities, 2025)
This study investigates the Indonesia-Australia Defence Cooperation Agreement (DCA) within the broader context of geopolitical dynamics in the Indo-Pacific. Employing a qualitative approach and political theory analysis, the research utilizes case study methods to assess the DCA’s implications for bilateral relations, ASEAN centrality, and regional stability. Drawing on official documents, academic publications, and policy reports, the study highlights how the DCA, signed in 2024, enhances defence cooperation through increased interoperability, joint military exercises, and maritime security collaboration. The findings reveal that while the agreement strengthens Indonesia’s defence capabilities and its leadership in ASEAN, it also poses challenges in balancing non-alignment policies and relations with major powers like China. This research underscores the DCA’s strategic significance as a framework for addressing regional security challenges, offering insights into its potential to shape future defence collaborations in the Indo-Pacific.